Development of capsular polysaccharide-based glycoconjugates for immunization against melioidosis and glanders - Burtnick, Mary N.; Heiss, Christian; Roberts, Rosemary A.; Schweizer, Herbert P.; Azadi, Parastoo; Brett, Paul J. (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia pseudomallei and Burkholderia mallei, the etiologic agents of melioidosis and glanders respectively, cause severe disease in humans and animals and are considered potential agents of biological warfare and terrorism. Diagnosis and treatment of infections caused by these pathogens can be challenging and, in the absence of chemotherapeutic intervention, acute disease is frequently fatal. At present, there are no human or veterinary vaccines available for immunization against these emerging/re-emerging infectious diseases. One of the long term objectives of our research, therefore, is to identify and characterize protective antigens expressed by B. pseudomallei and B. mallei and use them to develop efficacious vaccine candidates. Previous studies have demonstrated that the 6-deoxy-heptan capsular polysaccharide (CPS) expressed by these bacterial pathogens is both a virulence determinant and a protective antigen. Consequently, this carbohydrate moiety has become an important component of the various subunit vaccines that we are currently developing in our laboratory. In the present study, we describe a reliable method for isolating CPS antigens from O-polysaccharide deficient strains of B. pseudomallei; including a derivative of the select agent excluded strain Bp82. Utilizing these purified CPS samples, we also describe a simple procedure for covalently linking these T-cell independent antigens to carrier proteins. In addition, we demonstrate that high titer IgG responses can be raised against the CPS component of such constructs. Collectively, these approaches provide a tangible starting point for the development of novel CPS-based glycoconjugates for immunization against melioidosis and glanders.